The impact of cafes on the socialisation patterns and social interaction of young people in the digital era - Yos Sudarso; Kusnadi Kusnadi; Ary Purwatiningsih (Universitas Negeri Yogyakarta, 2026)
This study aims to examine the impact of cafes as gathering places for young people on their socialisation patterns and social interaction in the digital era. Using a mixed-methods approach, the study combines quantitative surveys, in-depth interviews, and observations of young people who frequently visit cafes. The findings indicate that cafes serve as important spaces for social interaction, both face-to-face and through digital media. Key findings highlight the benefits of cafes in facilitating social gatherings, discussions, and remote work, while also revealing negative impacts such as reduced quality of face-to-face communication due to digital device usage. This study contributes to understanding the role of cafes as hybrid spaces combining physical and digital interactions. Policy recommendations include promoting healthy face-to-face communication while leveraging cafes' positive potential to build social networks among young people.